A hunter-gatherer's guide to the 21st century : evolution and the challenges of modern life - Heying, Heather; Weinstein, Bret ([New York] : Portfolio/Penguin, 2021)
"For evolutionary biologists Heather Heying and Bret Weinstein, the cause of many modern woes is clear: the world is out of sync with humans' ancient brains and bodies. They distill more than twenty years of research and first-hand accounts from the most biodiverse ecosystems on Earth into straightforward principles and guidance for confronting our culture of hyper-novelty"--
Includes bibliographical references (pages 261-289) and index.
Keywords: Human ecology; Human evolution -- Social aspects; Civilization, Modern -- Social aspects; Hunting and gathering societies; Biodiversity